Efficacy of the Herpes Zoster Subunit Vaccine in Adults 70 Years of Age or Older - Cunningham, Anthony L; Lal, Himal; Kovac, Martina; Chlibek, Roman; Hwang, Shinn-Jang; Díez-Domingo, Javier; Godeaux, Olivier; Levin, Myron J; McElhaney, Janet E; Puig-Barberà, Joan; Vanden Abeele, Carline; Vesikari, Timo; et al. (The New England journal of medicine, 2016)
BACKGROUND: A trial involving adults 50 years of age or older (ZOE-50) showed that the herpes zoster subunit vaccine (HZ/su) containing recombinant varicella-zoster virus glycoprotein E and the AS01B adjuvant system was associated with a risk of herpes zoster that was 97.2% lower than that associated with placebo. A second trial was performed concurrently at the same sites and examined the safety and efficacy of HZ/su in adults 70 years of age or older (ZOE-70). METHODS: This randomized, placebo-controlled, phase 3 trial was conducted in 18 countries and involved adults 70 years of age or older. Participants received two doses of HZ/su or placebo (assigned in a 1:1 ratio) administered intramuscularly 2 months apart. Vaccine efficacy against herpes zoster and postherpetic neuralgia was assessed in participants from ZOE-70 and in participants pooled from ZOE-70 and ZOE-50. RESULTS: In ZOE-70, 13,900 participants who could be evaluated (mean age, 75.6 years) received either HZ/su (6950 participants) or placebo (6950 participants). During a mean follow-up period of 3.7 years, herpes zoster occurred in 23 HZ/su recipients and in 223 placebo recipients (0.9 vs. 9.2 per 1000 person-years). Vaccine efficacy against herpes zoster was 89.8% (95% confidence interval [CI], 84.2 to 93.7; P<0.001) and was similar in participants 70 to 79 years of age (90.0%) and participants 80 years of age or older (89.1%). In pooled analyses of data from participants 70 years of age or older in ZOE-50 and ZOE-70 (16,596 participants), vaccine efficacy against herpes zoster was 91.3% (95% CI, 86.8 to 94.5; P<0.001), and vaccine efficacy against postherpetic neuralgia was 88.8% (95% CI, 68.7 to 97.1; P<0.001). Solicited reports of injection-site and systemic reactions within 7 days after injection were more frequent among HZ/su recipients than among placebo recipients (79.0% vs. 29.5%). Serious adverse events, potential immune-mediated diseases, and deaths occurred with similar frequencies in the two study groups. CONCLUSIONS: In our trial, HZ/su was found to reduce the risks of herpes zoster and postherpetic neuralgia among adults 70 years of age or older. (Funded by GlaxoSmithKline Biologicals; ZOE-50 and ZOE-70 ClinicalTrials.gov numbers, NCT01165177 and NCT01165229 .).
Keywords: senioři; dvojitá slepá metoda; senioři nad 80 let; Double-Blind Method; Neuralgia, Postherpetic; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; Vaccines, Subunit; Kaplanův-Meierův odhad; Herpes Zoster; subjednotkové vakcíny; Aged, 80 and over; Herpes Zoster Vaccine; herpes zoster; vakcína proti pásovému oparu; ženské pohlaví; Humans; postherpetická neuralgie; lidé středního věku; Risk; riziko; Female; Aged; lidé; Male